STUDI TENTANG PEMBUATAN GULAI BUKEK PADA ACARA PERNIKAHAN (BARALEK) DI KECAMATAN MATUR KABUPATEN AGAM - Annisa Afantia; Lucy Fridayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this study is to describe the preparation of tools, preparation of materials, the process of making Gulai Bukek and the use of Gulai Bukek at weddings in Matur District, Agam Regency. This type of research is qualitative descriptive research with informant screening using snowball sampling techniques. Data was collected through observation, interviews and documentation and assisted by supporting instruments in the form of observation sheets and interview sheets. The techniques for checking the validity of this data and research are extension of participation, diligence of observation, triangulation, peer checking and auditing. The steps of analyzing data are data collection, data reduction, data presentation and data verification. The results showed that Gulai Bukek in Nagari Matua Hilia, Matur District, which is used as a food that must be served at every wedding (baralek) and has a unique taste and texture, which is thick like satay sauce and a distinctive goulash taste. The ingredients for making Gulai Bukek consist of cancang meat (swallow), rice flour, coconut rendang (ambu - ambu), jackfruit, bamboo shoots, red chilies, water, shallots, garlic, galangal, ginger, turmeric, candlenut, salt, goat cooker, cash - cash, bay leaves, orange leaves, lemongrass, turmeric leaves, oil. Equipment used in making Gulai Bukek includes, Material preparation equipment namely woven baskets (katidiang), knives, basins, cutting boards, plates. Gulai Bukek has a function, namely as a mandatory dish for invited guests, as samba / kapalo adaik (traditional food), as a campaign filler for people who have helped in the cooking process at home who have events, as a treat to ninik mamak.